The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15586/jkcvhl.v8i4.183
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Strict Trifecta Outcomes after Robot-Assisted Partial Nephrectomy: Comparison of RENAL, PADUA, and C-Index Scores

Abstract: Nephrometry scores are designed to characterize tumors and stratify the surgical complexity. It remains unclear as to which nephrometry score can accurately predict the surgical outcomes. We aimed to assess the utility of radius, exophytic/endophytic, nearness, anterior/posterior, location (RENAL), preoperative aspects and dimensions used for anatomic classifications (PADUA), and centrality index (C-index) nephrometry scores for predicting the strict Trifecta achievement from a single institution series roboti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
4
1
2
Order By: Relevance
“…в исследовании изучили возможность предсказания шкал RENAL, PADUA и C-index для достижения трифекты у 91 пациента, перенесшего роботическую резекцию опухоли почки. Все шкалы показали хорошую предиктивность достижения трифекты и были независимы друг от друга (площади под кривой (AUC) для RENAL, PADUA и C-index составили 0,782, 0,838 и 0,828 соответственно), а также ни одна шкала по своей результативности не уступала остальным [17].…”
Section: Discussionunclassified
“…в исследовании изучили возможность предсказания шкал RENAL, PADUA и C-index для достижения трифекты у 91 пациента, перенесшего роботическую резекцию опухоли почки. Все шкалы показали хорошую предиктивность достижения трифекты и были независимы друг от друга (площади под кривой (AUC) для RENAL, PADUA и C-index составили 0,782, 0,838 и 0,828 соответственно), а также ни одна шкала по своей результативности не уступала остальным [17].…”
Section: Discussionunclassified
“…In addition, multiple studies have analyzed the relationship between surgical approach and trifecta outcome [ 4 , 8 , 10 , 26 ]. In a direct comparison between open and robotic PN, Campi et al found that robotic PN was a significant predictor for achieving trifecta outcomes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…nephrometry score is an established anatomical system for categorizing complexity of renal tumors prior to surgery. Multiple studies have shown Nephrometry scores strongly correlate with effective PN [ 2 5 ] and predicts the attaining of “trifecta outcome” (reduced global renal ischemia, minimal complications, and high rates of negative margins) [ 4 , 6 ]. Herein, we evaluate the predictive value of individual components of the R.E.N.A.L scoring system for Laparoscopic (LPN) and Robotic Partial Nephrectomy (RPN).…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 16 20 22 ] Numerous studies have identified predictors of trifecta outcomes in relation to different surgical modalities and patient populations. Perioperative variables such as tumor size,[ 23 24 25 26 27 28 29 ] nephrometry scores (RNS,[ 27 30 31 ] PADUA score,[ 27 28 29 ] C-Index,[ 27 ] Simplified PADUA REnal [SPARE][ 32 ]), surgical approach,[ 23 33 ] pelvicalyceal system involvement,[ 23 ] hospital volume,[ 34 ] hilar location,[ 16 24 ] intraoperative blood loss,[ 24 28 35 ] and the American Society of Anesthesiologists grading[ 23 ] have been identified as independent predictors of the trifecta. However, apart from tumor complexity, none of the other factors have been consistently shown to predict these outcomes.…”
Section: Discussionmentioning
confidence: 99%